Extreme indifference - Rocío Lorca; Diego Rochow; Violeta Purán (Oñati Socio-Legal Series)
State punishment can only aspire to be a legitimate practice if it takes place within a fair political arrangement. As a consequence, some scholars have identified obstacles to justify punishment to those who are in the margins of the political relationship, such as foreigners. With the aim of identifying more precisely what these obstacles are in the specific case of foreigners, this article offers both a normative approach to the issue of punishing foreigners, and a description of the current situation of foreigners imprisoned in Chile. We argue that the Chilean prison system has high levels of illegitimacy in this regard, as it shows extreme indifference over the specific needs and pains of foreign prisoners.